2022
DOI: 10.1016/j.bioactmat.2021.07.030
|View full text |Cite|
|
Sign up to set email alerts
|

Fabrication of a bio-instructive scaffold conferred with a favorable microenvironment allowing for superior implant osseointegration and accelerated in situ vascularized bone regeneration via type H vessel formation

Abstract: The potential translation of bio-inert polymer scaffolds as bone substitutes is limited by the lack of neovascularization upon implantation and subsequently diminished ingrowth of host bone, most likely resulted from the inability to replicate appropriate endogenous crosstalk between cells. Human umbilical vein endothelial cell-derived decellularized extracellular matrix (HdECM), which contains a collection of angiocrine biomolecules, has recently been demonstrated to mediate endothelial cells(ECs) – osteoprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Decellularized extracellular matrix hydrogels, which may or may not contain cells, can be used as printing inks for three-dimensional bioprinting [ 245 , 246 , 247 ]. Other decellularization processes include decellularizing cornea to fabricate improved constructs [ 248 ], decellularizing human-umbilical-vein-endothelial-cell (HUVEC)-derived extracellular matrix to be integrated into a manufactured scaffold with collagen type I to improve endothelial cells with progenitor cell crosstalk due to their intact angiocrine biomolecules for osseointegration [ 249 ], and decellularizing rat livers to form acellular 3D bioscaffolds suitable for seeding with induced pluripotent stem cells (iPSCs) [ 250 ]. The focus of research may vary depending on the technology and application, but the fundamental use of collagen type I is undeniable.…”
Section: Current Insights and Conclusionmentioning
confidence: 99%
“…Decellularized extracellular matrix hydrogels, which may or may not contain cells, can be used as printing inks for three-dimensional bioprinting [ 245 , 246 , 247 ]. Other decellularization processes include decellularizing cornea to fabricate improved constructs [ 248 ], decellularizing human-umbilical-vein-endothelial-cell (HUVEC)-derived extracellular matrix to be integrated into a manufactured scaffold with collagen type I to improve endothelial cells with progenitor cell crosstalk due to their intact angiocrine biomolecules for osseointegration [ 249 ], and decellularizing rat livers to form acellular 3D bioscaffolds suitable for seeding with induced pluripotent stem cells (iPSCs) [ 250 ]. The focus of research may vary depending on the technology and application, but the fundamental use of collagen type I is undeniable.…”
Section: Current Insights and Conclusionmentioning
confidence: 99%
“…Culture in a 3D bioprinted scaffold with unique nanostructures and enhanced further the proliferation of hBMSCs in the dGQH 20 @Exo group in comparison to all other groups. Therefore, the beneficial physical structure and bioactive factors are both required to foster an angiogenic-osteogenic microenvironment for accelerating bone regeneration [90].…”
Section: In Vitro Biological Properties Of the Dgqh 20 @Exo Scaffoldsmentioning
confidence: 99%
“…Endothelial cell dECMs promote angiogenesis in the bone microenvironment. In vivo research revealed the importance of vascular infiltration and bone regeneration using a hybrid PCL/fibronectin/dECM scaffold (PFE) made from HUVEC-derived dECMs (HdECM), demonstrating that the environmental signals in the dECM could induce angiogenesis and osteogenesis [ 97 ].…”
Section: Application Of Decm-derived Bioinks In 3d Bioprintingmentioning
confidence: 99%